2017
DOI: 10.1177/1474704917742807
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Memory: Remembering Potential Mates

Abstract: According to the adaptive memory perspective, memory should function more efficiently in fitness-relevant domains. The current work explored whether there is a mnemonic tuning in a fundamental domain for human evolution: reproduction. In two experiments, female participants assessed how desirable potential male candidates (represented by a face and a short descriptor) would be in the context of a long-term mating relationship or in the context of a long-term work relationship. Then, after a short distractor ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…adopted vs biological) can influence recall (Bonin, Gelin, Laroche, & Méot, 2019;Seitz, Polack, & Miller, 2020, but see Krause et al, 2019). Other studies have demonstrated preferential memory for items potentially contaminated by a sick individual (Bonin, Thiebaut, Witt, & Méot, 2019;Fernandes, Pandeirada, Soares, & Nairne, 2017;Gretz & Huff, 2019) and for finding a mate (Pandeirada, Fernandes, Vasconcelos, & Nairne, 2017). Taken together, these and other studies suggest that the evolutionary significance of information encoded positively influences future recallability (Seitz et al, 2019).…”
Section: Is There a Memory Bias For High-calorie Food Images?mentioning
confidence: 89%
“…adopted vs biological) can influence recall (Bonin, Gelin, Laroche, & Méot, 2019;Seitz, Polack, & Miller, 2020, but see Krause et al, 2019). Other studies have demonstrated preferential memory for items potentially contaminated by a sick individual (Bonin, Thiebaut, Witt, & Méot, 2019;Fernandes, Pandeirada, Soares, & Nairne, 2017;Gretz & Huff, 2019) and for finding a mate (Pandeirada, Fernandes, Vasconcelos, & Nairne, 2017). Taken together, these and other studies suggest that the evolutionary significance of information encoded positively influences future recallability (Seitz et al, 2019).…”
Section: Is There a Memory Bias For High-calorie Food Images?mentioning
confidence: 89%
“…Over the past decade following Nairne et al's (2007) publication reporting on the survival processing effect, a large number of other mnemonic biases that appear to reflect selective pressures have been discovered. These involve biases with respect to remembering potential sources of contamination (Bonin et al, 2019;Fernandes et al, 2017;Gretz & Huff, 2019), remembering animate versus inanimate objects (Gelin, Bonin, Méot, & Bugaiska, 2018;Nairne, VanArsdall, & Cogdill, 2017;Nairne, VanArsdall, Pandeirada, Cogdill, & LeBreton, 2013), remembering suspicious characters (Hou & Liu, 2019), and remembering items relevant to raising ones child (Seitz et al, 2018) or finding a mate (Pandeirada et al, 2017; for a review, see Seitz et al, in press). These findings are suggestive of general evolutionary constraints to memory, and Seitz et al (in press) suggested there exists a positive relationship between the perceived fitness value of information and its likelihood of being remembered.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence that memory can be influenced by aspects of human mating outside of the survival processing paradigm. For example, Pandeirada, Fernandes, Vasconcelos, and Nairne (2017) found enhanced memory for the descriptions of individuals being evaluated as potential long-term mates compared to those same descriptions if the individual is being evaluated as a potential coworker. Baker, Nicole Sloan, Hall, Leo, and Maner (2015) found increased recall for details of a story when men were also viewing images of attractive faces of the opposite sex compared to average faces of the opposite sex and that these effects were not driven by changes in arousal or mood.…”
Section: And Effects Of Biological Relatedness On Recallmentioning
confidence: 99%
“…As an example, simply imagining oneself performing fitness relevant tasks, such as surviving in the grasslands or parenting a child, while encoding information, can result in increased retention of that information (Nairne, Thompson, & Pandeirada, 2007;Seitz, Polack, & Miller, 2018). There are also reported biases towards remembering potential sources of contamination (Bonin, Thiebaut, Witt, & Méot, 2019;Fernandes, Pandeirada, Soares, & Nairne, 2017), future mates (Pandeirada, Fernandes, Vasconcelos, & Nairne, 2017), and potentially untrustworthy individuals (Hou & Liu, 2019;Kroneisen, 2018). Thus, it appears the evolutionary significance of encoded information potentiates its ability to be later recalled (Seitz, Blaisdell, Polack, et al, 2019).…”
Section: Special Status Of Memory Of Eatingmentioning
confidence: 99%